Glucocorticoid receptor blockade normalizes hippocampal alterations and cognitive impairment in streptozotocin-induced type 1 diabetes mice - Revsin, Yanina (2009)
Type 1 diabetes is a common metabolic disorder accompanied by an increased secretion of glucocorticoids and cognitive deficits. Chronic excess of glucocorticoids per se can evoke similar neuropathological signals linked to its major target in the brain, the hippocampus. This deleterious action exerted by excess adrenal stress hormone is mediated by glucocorticoid receptors (GRs). The aim of the present study was to assess whether excessive stimulation of GR is causal to compromised neuronal viability and cognitive performance associated with the hippocampal function of the diabetic mice. For this purpose, mice had type 1 diabetes induced by streptozotocin (STZ) administration (170 mg/kg, i.p.). After 11 days, these STZ-diabetic mice showed increased glucocorticoid secretion and hippocampal alterations characterized by: (1) increased glial fibrillary acidic protein-positive astrocytes as a marker reacting to neurodegeneration, (2) increased c-Jun expression marking neuronal activation, (3) reduced Ki-67 immunostaining indicating decreased cell proliferation. At the same time, mild cognitive deficits became obvious in the novel object-placement recognition task. After 6 days of diabetes the GR antagonist mifepristone (RU486) was administered twice daily for 4 days (200 mg/kg, p.o.). Blockade of GR during early type 1 diabetes attenuated the morphological signs of hippocampal aberrations and rescued the diabetic mice from the cognitive deficits. We conclude that hippocampal disruption and cognitive impairment at the early stage of diabetes are caused by excessive GR activation due to hypercorticism. These signs of neurodegeneration can be prevented and/or reversed by GR blockade with mifepristone. © 2009 Nature Publishing Group All rights reserved.